2013
DOI: 10.1088/0004-6256/145/3/77
|View full text |Cite
|
Sign up to set email alerts
|

STELLAR POPULATIONS AND EVOLUTION OF EARLY-TYPE CLUSTER GALAXIES: CONSTRAINTS FROM OPTICAL IMAGING AND SPECTROSCOPY OFz= 0.5–0.9 GALAXY CLUSTERS

Abstract: We present an analysis of stellar populations and evolutionary history of galaxies in three similarly rich galaxy clusters MS0451.6-0305 (z = 0.54), RXJ0152.7-1357 (z = 0.83), and RXJ1226.9+3332 (z = 0.89). Our analysis is based on high signal-to-noise ground-based optical spectroscopy and Hubble Space Telescope imaging for a total of 17-34 members in each cluster. Using the dynamical masses together with the effective radii and the velocity dispersions we find no indication of evolution of sizes or velocity d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

31
218
5
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 75 publications
(255 citation statements)
references
References 106 publications
(221 reference statements)
31
218
5
1
Order By: Relevance
“…Our results for the size evolution partly disagree with a recent work by Jørgensen et al (2014), where almost no size variation with redshift is found from their sample of clusters at z 1 < (from e.g., Jørgensen & Chiboucas 2013); their cluster at z 1.27 > shows trends similar to ours, suggesting that larger effects of size-evolution can be seen at z 1 > . We note that the difference with the cluster sample at z 1 < could also be related to the different selections used in our sample and the sample of Jørgensen et al (2014).…”
Section: Size-mass and Stellar Velocity Dispersion-mass Relationscontrasting
confidence: 99%
See 2 more Smart Citations
“…Our results for the size evolution partly disagree with a recent work by Jørgensen et al (2014), where almost no size variation with redshift is found from their sample of clusters at z 1 < (from e.g., Jørgensen & Chiboucas 2013); their cluster at z 1.27 > shows trends similar to ours, suggesting that larger effects of size-evolution can be seen at z 1 > . We note that the difference with the cluster sample at z 1 < could also be related to the different selections used in our sample and the sample of Jørgensen et al (2014).…”
Section: Size-mass and Stellar Velocity Dispersion-mass Relationscontrasting
confidence: 99%
“…We test that our M L log are consistent with the the M L log we derive by fitting a linear relation between the logarithms of the age, metallicity, and M/L of Maraston (2005) SSPs with an age 1 Gyr and metallicity Z Z log  between −0.3 and 0.3 (total metallicity relative to solar), as done in Jørgensen et al (2005), Jørgensen & Chiboucas (2013), and Jørgensen et al (2014). In the following, we adopt the M L log obtained via interpolation of the SSPs because the relation between M/L and age log becomes strongly nonlinear at young ages, which could potentially make our linear relation more uncertain.…”
Section: Formation Ages From the M/l Ratio Evolutionmentioning
confidence: 80%
See 1 more Smart Citation
“…Based on deep, medium-resolution IMACS spectroscopy of a sample of ∼ 70 massive galaxies at z = 0.7, we characterize for the first time at these redshifts the stellar metallicity and age scaling relations for the population as a whole and for quiescent and star-forming galaxies separately We find that z = 0.7 quiescent galaxies have stellar metallicities and stellar ages consistent with local quiescent galaxies under passive evolution hypothesis, in qualitative agreement with results on cluster quiescent galaxies by Sánchez-Blázquez et al (2009) and Jørgensen & Chiboucas (2013). However, we also show that the scatter in age of z = 0.7 quiescent galaxies is too low to reproduce the scatter of the local relation.…”
Section: Discussionsupporting
confidence: 81%
“…Most of these works target red-sequence galaxies in clusters (e.g. Sánchez-Blázquez et al 2009;Jørgensen & Chiboucas 2013) and find their properties to be consistent with passive evolution at high masses. So far only few works have presented the ages and metal abundances of massive quiescent galaxies in the field at z 0.7 (Schiavon et al 2006;Gallazzi et al 2014;Choi et al 2014).…”
Section: Introductionmentioning
confidence: 99%